Up-regulation of lncRNAs in peripheral blood mononuclear cells of patients with pancreatic cancer - Mosharraf Ghahfarokhi, Arezoo; Abedi Kichi, Zahra; Sheidaei, Masoud; Shirvani-Farsani, Zeinab (Gene reports, 2023)
Pancreatic cancer (PC) is a highly concerning human malignancy all over the World, its incidence has been increasing rapidly in recent decades. The possible therapeutic target has yet to be discovered. Currently, available studies have shown that long noncoding RNAs (lncRNAs) are associated with cancer development, progression, and metastasis, while the details of these mechanisms are yet unknown. In the current study, we analyzed the expression of five lncRNAs; CTD903, LINC00092, MIF, PCGEM1, and LINK-A in patients with pancreatic cancer and healthy subjects' peripheral blood using quantitative real-time PCR. Literature study and the UCSC Genome Browser were used to select candidate lncRNAs. Quantitative real-time PCR (qPCR) analysis was employed to detect mentioned lncRNAs. The correlation between candidate lncRNA expression with clinical and pathological features was also examined. We found that levels of CTD903 and LINC00092 were significantly higher in the blood of PC patients than in healthy subjects. Remarkably, the results indicated that the expression of CTD903 and PCGEM1 was significantly higher in male patients than in male controls. LINC00092 was also different between sex-based subgroups and it was higher in both males and females with PC than healthy ones. Our data show a significant difference in the expressions of CTD903 and LINC00092 were significantly higher in patients in <60 subgroups compared with controls in these subgroups. Moreover, a positive correlation was found between the expression of mentioned lncRNAs. Additionally, based on the ROC curve analysis, diagnostic powers of CTD903 and LINC00092 in PC were 0.63 and 0.65, respectively. The present study shows pieces of evidence for the participation of CTD903 and LINK00092 in the pathophysiology of pancreatic cancer. •Increased expression of CTD903 and LINC00092 in patients with pancreatic cancer•Upregulation of CTD903 and PCGEM1 in male patients compared to male controls•LINC00092 was higher in both males and females with PC than healthy ones.•The area under the ROC curve (AUC) for CTD903 and LINC00092 was significant.•These lncRNAs may play a critical role in the pathology of pancreatic cancer.